Living With Cancer Reflected In John Green's The Fault In Our Stars (2012): A Humanistic Psychology Approach - Wulandari, Wheny, Dr. M. Thoyibi,M.S, Titis Setyabudi,S.S. M. Hum (2016)
This study is about Living with Cancer in John Green's The Fault in Our Stars (2012) which is analyzed by using Humanistic Psychology approach. The objectives of the study are to know the first response of every character when they know they get cancer, how the characters live with cancer, and the writer concerns about the cancer part based on humanistic psychological approach by Carl Rogers. This research belongs to qualitative research. The primary data of this research is The Fault in Our Stars by John Green's in 2012, while the secondary data of this research are other sources related to the study, such as: website, dictionary and some books which support this research. The researcher draws three conclusions in this research. First is the response of person when they know they get cancer. Second is that cancer patient would feel desperate and lost their hope to live. Third is that in the novel, the author wants to support the cancer patient to live with cancer, not to give up. Keywords: Cancer, The Fault in Our Stars, Humanistic Psychological